2020
DOI: 10.1016/j.omto.2020.07.011
|View full text |Cite
|
Sign up to set email alerts
|

miR-324-5p Contributes to Cell Proliferation and Apoptosis in Pancreatic Cancer by Targeting KLF3

Abstract: Pancreatic cancer cells are characterized by high cell proliferation and low cell apoptosis, but the factors involved in these processes remain to be further studied. In this study, we report that miR-324-5p regulates the proliferation and apoptosis of pancreatic cancer cells through regulating the expression of Krüppel-like factor 3 (KLF3). In both pancreatic cancer tissues and cell lines, the levels of miR-324-5p are significantly increased. Inhibition of miR-324-5p represses cell proliferation but promotes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…According to in vitro and in vivo research, KLF3 inhibition accelerates lung cancer EMT and promotes lung cancer metastasis through the STAT3 signalling pathway [ 26 ]. Overexpression of KLF3 suppressed cell proliferation and increased apoptosis in vitro, and it has also been demonstrated to be downregulated in human pancreatic cancer [ 27 ]. In our study, KLF3 expression levels in human CRC were shown to be lower than in normal tissues, and the results of univariate and multivariate Cox regression analysis suggested that KLF3 was associated with a better prognosis in CRC patients.…”
Section: Discussionmentioning
confidence: 99%
“…According to in vitro and in vivo research, KLF3 inhibition accelerates lung cancer EMT and promotes lung cancer metastasis through the STAT3 signalling pathway [ 26 ]. Overexpression of KLF3 suppressed cell proliferation and increased apoptosis in vitro, and it has also been demonstrated to be downregulated in human pancreatic cancer [ 27 ]. In our study, KLF3 expression levels in human CRC were shown to be lower than in normal tissues, and the results of univariate and multivariate Cox regression analysis suggested that KLF3 was associated with a better prognosis in CRC patients.…”
Section: Discussionmentioning
confidence: 99%
“…MiR‐324‐5p has been reported to regulate cell proliferation and apoptosis under diverse conditions by targeting different mRNAs (Wang et al , 2015 ; Lin et al , 2018 ; Chen et al , 2019b ; Wan et al , 2020 ; Zheng et al , 2021 ). For example, miR‐324‐5p inhibits mitochondrial fusion and apoptosis in cardiomyocytes and endothelial progenitor cells by downregulating Mtfr1 (Wang et al , 2015 ; Chen et al , 2019b ; Huang et al , 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, exogenous miR-93-5p promotes EC cell proliferation and communication by targeting Pten. MiR-324-5p may promote the progression of thyroid, oropharyngeal, pancreatic, and lung cancer cells, polarized M2 macrophages in colon cancer, and modulated the microenvironment in thyroid cancer ( Wan et al, 2020 ). However, the functions of miR-324-5p in EC remain unclear.…”
Section: Discussionmentioning
confidence: 99%